Challenges and opportunities to conduct a smart Supply Chain management in oil and Gas Industry with a sustainable strategies (Journal of Informatics Education and Research, 2023)
The smarter energy supply chain is a management approach for the energy supply chain that is genuinely end-to-end, fully integrated, coordinated, and data-driven. Managing the supply chain as a whole requires time and money to establish the necessary organisational framework, policies, services, and assets. Through the use of intelligent supply chain management, the finest possible lines of communication may be established with distributors and end users. Strategically configuring the relationships between oil and gas firms' various suppliers and customers requires the establishment of boundaries and parameters. Research, discussion, and analysis are conducted through personal interviews and correspondence with oil industry professionals via mail, communication, literature surveys, and journals. Two case studies are considered and discussed to aid in supply chain management for two separate oil sectors. Important factors in supply chain management include demand management, effective distribution of petroleum products among consumers, improved transportation scheduling, warehouse management, and the quality and timeliness of information provided by supply chain automation. If a supplier continually outperforms the competition, they should be rewarded with favourable status, such as customer loyalty and special treatment.  There is no just-in-time (JIT) in oil and gas exploration and production, which is a major factor in supply-chain management. It's comparable to feeding a small city to supply an offshore platform. That's why it's crucial to always plan ahead for what will be required beyond the obvious basics and regular supply.